The long and short of mistress relationships: Sex-differentiated mate preferences reflect a compromise of mating ideals - CHOY, Bryan K. C. (Institutional Knowledge at Singapore Management University, 2022)
The mate preferences literature has been fairly muted on mate preferences for extrapair partners. In four studies, we examined mate preferences for mistress relationships--the traits that men prioritize in a mistress and that mistresses prioritize in their male partners--and compared these preferences to those of short- and long-term relationships. In studies 1a and 1b, (N = 104 and 191 respectively), we derived dimensions of mate preferences for mistress relationships through factor analyses. In studies 2 and 3 (N = 219 and 101 respectively) we employed the budget allocation paradigm to compare people's priorities for different traits for a mistress relationship (versus short- and long-term relationships). We found that men focused on fulfilling short-term mating ideals (prioritizing physical attractiveness) in a mistress relationship, but women focused on fulfilling longer-term (but also some short-term) mating ideals (prioritizing both physical attractiveness and social status) for a mistress relationship. Overall, mistress relationships may reflect a compromise of men's and women's conflicting and evolved mating ideals.